Comparison of Outcome of Appendectomy: Laparoscopic versus Open Surgery in Combined Military Hospital, Savar (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Open appendectomy and laparoscopic appendectomy are two modalities in the treatment of appendicitis. Superiority of one over another is not clear.Objectives: To compare per-operative and post operative outcomes between open and laparoscopic appendectomy.Material and Methods: Prospective comparative study was conducted on patients with acute appendicitis who underwent open appendectomy (OA) (n=43) or laparoscopic appendectomy (LA) (n=59) from October 2018 to October 2019 in Combined Military Hospital (CMH), Savar. The two groups were compared in respect to patients' characteristics, duration of operation, operative findings, post operative pain, return of peristalsis, resume of oral feeding, post operative complications, return to activities and cosmesis. Statistical analysis was performed using SPSS 25.0. Continuous and categorical variables were analyzed using independent sample t test and chi-square test respectively and p